Permanent magnet flux switching motor technology as a solution for high torque clean electric vehicle drive - Enwelum I. Mbadiwe; Erwan Sulaiman; Zarafi Md. Ahmad; M.F. Omar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
A breakthrough in this century has been the development of electric vehicle which is propelled by electric motor powered by electricity. Already, many electric motors have been used for electric vehicle application but performances are low. In this paper, a permanent magnet motor technology using unconventional segmented rotor for high torque application is presented. Unlike conventional motors, this design, flux switching motor (FSM) is an advance form of synchronous machine with double rotating frequency. It accommodates both armature winding and flux source on the stator while the rotor is a simple passive laminated sheet steel. Conventionally, rotor of the maiden FSM and many emerging designs have focused on the salient pole, this design employs segmented rotor. Segmented rotor has advantages of short flux path more than salient rotor pole resulting in high flux linkage. Geometric topology of the proposed motor is introduced. It consists of 24Stator-14Pole using PM flux source with alternate stator tooth armature winding. The 2D-FEA model utilized JMAG Tool Solver to design and analyze motor’s performance in terms of torque with average torque output of 470Nm. The suitability of segmented outer-rotor FS motor as a high torque machine, using permanent magnet technology is a reliable candidate for electric vehicle.